UPAYA PENINGKATAN PRESTASI BELAJAR PADA PESERTA DIDIK DI SMK NEGERI 1 PATI - Hayati, Nur; Wuryandini, Endang; Yunus, Mahmud (MAJALAH LONTAR, 2022)
This study aims to analyze the principal's policies, teacher efforts and student efforts in improving learning achievement. The research method is descriptive qualitative. Data collection instruments used interview guidelines, observation sheets and documentation. Test the validity of the data using technical triangulation and source triangulation. The data analysis technique uses Miles and Huberman interactive analysis: data collection, data condensation, data display, and conclusion drawing/verification. The results of the research include: Schools in collaboration with DUDI (Industrial World Business) in accordance with expertise competencies; Principal's policy to increase accreditation; Principals provide guidance and training to teachers in accordance with the areas of competence being taught; Principal conducts academic evaluation and supervision; Teachers participate in training and IHT activities; The teacher conducts a survey of students; Teachers provide training, coaching and motivation to students; Teachers use digital media such as Canva to train students' skills; Students participate in training and coaching activities in entrepreneurship activities; Students listen and understand the material explained by the teacher; Students work on and submit assignments on time.